A política de cotas na Universidade Federal do Ceará: processo de implementação e cotistas - Nascimento, Aparecida do Ó do (2016)
This is a work on the implementation process of the quota policy at the Federal University of Ceará - UFC, discussions began in 2005, but the execution materialized in 2012, after enactment of Law No. 12,711 / 2012, which makes policy compulsory in Federal Institutions of Higher Education. The design of runs through research by discussions analysis originated on the national scene in the period prior to this Law in order to understand the unfolding of the long process of implementation of this policy in the UFC and expectations with the changes brought about by the adoption of quotas. Thus, the overall objective of the research is to analyze what kind of changes related to student access inequalities were boosted with the implementation of the quota policy, particularly as regards the socio-economic and cultural profile of the students of the most competitive courses and high prestige social. The study also includes important contributions about the degree of satisfaction of students with the course, academic performance and relationships with classmates. For this, the research includes the following specific objectives: 1) Discuss the process of affirmative action institution in selection processes of Brazilian Higher Education Institutions and its impact recorded in previous studies; 2) Analyze the process of discussion on implementation of quotas in the UFC; 3) From a sample of UFC courses, investigate the socioeconomic and cultural profile of the students; 4) Analyze comparatively student quota and no student quota within the selected courses. The information for the survey are the result of access to documentary sources, such as ATA and reports, intense empirical research with primary data collection.